2015
DOI: 10.1016/j.oregeorev.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated rare-element mineralization in an ongonite–topazite composite dike at the Xianghualing tin district, Southern China: An electron-microprobe study on the evolution from niobium–tantalum-oxides to cassiterite

Abstract: , et al.. Differentiated rare-element mineralization in an ongonite -topazite composite dike at the Xianghualing tin district, Southern China: an electron-microprobe study on the evolution from niobium-tantalum-oxides to cassiterite. Ore Geology Reviews, Elsevier, 2015Elsevier, , 65, pp.761-778. <10.1016Elsevier, /j.oregeorev.2014.08.008>. Differentiated rare-element mineralization in an ongonite-topazite composite dike at the Xianghualing tin district, Southern China: An electron-microprobe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In addition, fluids derived from mantle‐derived magmas underplated in the lower crust, which are inferred to have provided most of the heat for generating the crustal melts and Jurassic granites in South China (e.g., Li et al, , ; Zhao et al, ), could have played a role as well, though such fluids would have been CO 2 ‐rich, while we infer low CO 2 contents for the main granite magmas with X H 2 O > 0.7 during most of its crystallization (compare Figures and ). Based on the composition of the natural Bt crystals, melt fluorine contents appear to have been ~0.2 wt % and thus moderately high during Bt crystallization (using a ( D F Bt/melt ) partition coefficient of 3.7 according to Icenhower and London (), but significantly below saturation (at several wt %; Bailey, ; Huang et al, ) until late‐stage crystallization. The fact that experimental Amps also have similar F contents than their natural counterparts further shows that F content in the experiments was similar to that in the magma (Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fluids derived from mantle‐derived magmas underplated in the lower crust, which are inferred to have provided most of the heat for generating the crustal melts and Jurassic granites in South China (e.g., Li et al, , ; Zhao et al, ), could have played a role as well, though such fluids would have been CO 2 ‐rich, while we infer low CO 2 contents for the main granite magmas with X H 2 O > 0.7 during most of its crystallization (compare Figures and ). Based on the composition of the natural Bt crystals, melt fluorine contents appear to have been ~0.2 wt % and thus moderately high during Bt crystallization (using a ( D F Bt/melt ) partition coefficient of 3.7 according to Icenhower and London (), but significantly below saturation (at several wt %; Bailey, ; Huang et al, ) until late‐stage crystallization. The fact that experimental Amps also have similar F contents than their natural counterparts further shows that F content in the experiments was similar to that in the magma (Table S7).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Processes related to the evolution of the melt Experimental and fluid/melt inclusion studies have demonstrated that during the last stage of magmatic crystallization, an exsolution process can occur, resulting in up to three products, namely, a silicate melt, vapour and a hydrosaline phase, the latter being described either as a fluid (Roedder, 1992;Kamenetsky et al, 2004;Alfonso and Melgarejo, 2008;Tartese and Boulvais, 2010;Chicharro et al, 2015;Webster et al, 2015;Assadzadeh et al, 2017) or as a melt (Badanina et al, 2004;Veksler, 2004;Thomas and Davidson, 2013;Huang et al, 2015).…”
Section: S214mentioning
confidence: 99%
“…The Nb-Ta oxides are hosted by the silicate matrix, and display a simple core-rim normal progressive zoning and less frequently an oscillatory zoning (Figure 7). The presence of these oxides as inclusions within most primary minerals, such as muscovite and albite; as well as the inclusion of some albite within the coltan ( Figure 6), and chemical zoning of these oxides (Figure 7) allow for interpreting these crystals as magmatic in origin, as described in worldwide studies [4,6,9,10,12,28,36,37,105,[125][126][127][128]. CGM-I is characterized by high Mn# (0.52-0.89) and low Ta# (0.04-0.19) typical of earlier magmatic-stage products, and the observed differences in Mn# or Ta# values of the primary columbite minerals in the different facies strongly suggest a high differentiated magmatic environment during crystallization of the Mayo Salah leucogranite magma (Figure 8; [12]).…”
Section: The Mayo Salah Pluton: a Peraluminous Low-phosphorous Rare-mmentioning
confidence: 99%